Synthetic heparan sulfate ligands for vascular endothelial growth factor to modulate angiogenesis - Jain, Prashant; Shanthamurthy, Chethan D.; Leviatan Ben-Arye, Shani; Yehuda, Sharon; Nandikol, Sharvani S.; Thulasiram, V, Hirekodathakallu; Padler-Karavani, Vered; Kikkeri, Raghavendra (Chemical Communications, 2021)
We report the discovery of a potential heparan sulfate (HS) ligand to target several growth factors using 13 unique HS tetrasaccharide ligands. By employing an HS microarray and SPR, we deciphered the crucial structure-binding relationship of these glycans with the growth factors BMP2, VEGF(165), HB-EGF, and FGF2. Notably, GlcNHAc(6-O-SO3-)-IdoA(2-O-SO3-) (HT-2,6S-NAc) tetrasaccharide showed strong binding with the VEGF(165) growth factor. In vitro vascular endothelial cell proliferation, migration and angiogenesis was inhibited in the presence of VEGF(165) and HT-2,6S-NAc or HT-6S-NAc, revealing the potential therapeutic role of these synthetic HS ligands.